Anti-theft door lock system / Ummar Muhammad & Mohamad Hairul Ariffin Mohd Shukor - Muhammad, Ummar; Mohd Shukor, Mohamad Hairul Ariffin (2015)
In recent years, cases of house break-ins increased dramatically. This causes anxiety in the population of Malaysia to overcome this problem. A system will be proposed to deal with this widespread matter. The system is called as the anti-theft door lock system. The system utilizes the latest technology of improving the conventional locking system that currently used. Therefore by using this system, the burglary cases can be reduced and the safety of Malaysians residential is guaranteed. The regular door lock system possesses a lackness to be easily be breached-in and sometimes the doorknob is stuck causes the door is hard to be opened. The magnet is used as an actuator to open and close the door. By keying the pin number which been programmed earlier, the magnet will demagnetize and the door will be opened if the pin number entered is correct. Otherwise if the pin number entered is wrong then the door will not able to be opened. The simulation is performed using proteus software and micro c programming for programming the controller. The expected results for this project is when the correct password is entered the relay will act as 'normally open' therefore the magnet will be demagnetized and the door can be opened